Determination of Heating Value of Estonian Oil Shale by Laser-Induced Breakdown Spectroscopy. (9th January 2018) - Aints, M.; Paris, P.; Laan, M.; Piip, K.; Riisalu, H.; Tufail, I.
Abstract : The laser-induced breakdown spectroscopy (LIBS) combined with multivariate regression analysis of measured data were utilised for determination of the heating value and the chemical composition of pellets made from Estonian oil shale samples with different heating values. The study is the first where the oil shale heating value is determined on the basis of LIBS spectra. The method for selecting the optimal number of spectral lines for ordinary multivariate least squares regression model is presented. The correlation coefficient between the heating value predicted by the regression model, and that measured by calorimetric bomb, was R 2 = 0.98 . The standard deviation of prediction was 0.24 MJ/kg. Concentrations of oil shale components predicted by the regression model were compared with those measured by ordinary methods.